Straight from the heart - Hoag, Tami (Detroit : Large Print Press, 2007)
When Jace Cooper shows up in her physical therapy department needing medical attention after leaving her seven years ago, Rebecca Bradshaw finds herself falling for him again as she helps him repair his broken body and fractured past.
Keywords: Physical therapist and patient; Large type books; Love stories